Determinan Kesuksesan Sistem Informasi Akuntansi: Studi Persepsional di Lembaga Pendidikan Dasar Muhammadiyah - Virana, Tiara Anindya; Sutopo, Bambang (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
This study aims to identify the factors that influence the success of Accounting Information Systems (AIS) in Muhammadiyah primary education institutions.The perceptual approach is used to measure the opinions of AIS users. The research method used was a survey through questionnaires distributed to 100 respondents from various Muhammadiyah elementary schools in Surabaya city. Data analysis was conducted using descriptive statistical methods and Partial Least Square to identify the main factors of AIS success. The results showed that information quality had no significant effect on satisfaction and use of accounting systems, while service quality also had no significant effect on satisfaction and system quality had no significant effect on the use of accounting information systems. This study provides recommendations for improving accounting information systems in basic education institutions and provides practical insights by providing theoretical insights into the key factors that influence the successful implementation of such systems.